Dinamika Dakwah Komunitas Sahabat Akhirat - Fitria Nazilatullail; Mukhlis Aliyudin; Asep Shodiqin (Department of Islamic Communication and Broadcasting, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2020)
Penelitian ini memiliki tujuan untuk mengetahui lebih jauh mengenai kegiatan dakwah komunitas Sahabat Akhirat di Kabupaten Purwakarta dilihat dari segi bentuk aktivitas dakwah, proses pelaksanaan dakwah dan materi dakwahnya. Penelitian ini menggunakan metode deskriptif dengan mendapatkan sumber data secara premier dan sekunder. Analisis data dengan analisis kualitatif. Hasil penelitian menjelaskan bahwa komunitas Sahabat Akhirat menggunakan bentuk aktivitas dakwah yaitu tabligh, proses pelaksanaan dakwah dilakukan dengan tiga tahapan dakwah yaitu tahap pembentukan dan perkenalan, tahap penataan dakwah dan tahap kemandirian. Materi dakwah yang disampaikan oleh komunitas Sahabat Akhirat mengenai materi akidah, ibadah, akhlak dan untuk tetap selalu membiasakan membaca al-qur’an serta bersedekah. This paper is made with the aim of knowing more about the da'wah activities of the Sahabat Akhirat community in Purwakarta Regency in terms of the form of da'wah activities, the process of carrying out the da'wah and its da'wah materials. This research method uses a descriptive method involving premier and secondary data sources. Data analysis with qualitative analysis. The results of the study explained that the Sahabat Hereafter community uses a form of preaching activity, namely tabligh, the process of carrying out da'wah is carried out in three stages of preaching, namely the formation and introduction stage, the da'wah structuring stage and the independence stage. The da'wah material delivered by the Sahabat Hereafter community is about the material of faith, worship, morals and to always get used to reading al-quran and giving alms.